Ultrafine denier regenerated cellulose fiber and preparation method thereof
By adding plasticizer and thickener to the spinning solution and separating polymer substances in the fiber feeding tank, the problem of total draft control difficulty of fine denier and ultrafine denier regenerated cellulose fibers is solved, and the fiber fine is achieved Improvements in degree and intensity simplify production processes and reduce costs.
Patent Information
- Application Number
- CN202310367814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-04-07
AI Technical Summary
In the prior art, when preparing fine denier and ultrafine denier regenerated cellulose fibers, the overall draft control is difficult, which can easily lead to a decrease in the dry elongation of the fiber, an increase in the broken wire, a low dry strength of the fiber, and an increase in defects, and a high production cost.
By adding plasticizer and thickener to the spinning solution, adjust the content of cellulose and the mass ratio of polymer substances, ensure the draft plasticity during the spinning process, and complete the polymer substance and fibers in the fiber feeding tank. The separation of the macromolecular substance removal process reduces the post-treatment.
The fineness of the fiber is improved to 0.33-0.55dtex, the dry fracture strength is 2.00-2.60cN/dtex, and the wet fracture strength is 1.00-1.40cN/dtex. The moisture absorption and breathability of the fiber are improved and the softness of the hand feel is simplified, which simplifies production. Process and reduce costs.
Smart Images

Figure CN116356442B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to an ultra-fine denier regenerated cellulose fiber and a preparation method thereof. Background Art
[0002] The development and research of fine denier fiber has always been one of the research directions of fiber differentiation, and it is a representative of the development of chemical fiber towards high technology and high simulation. Fine denier and ultra-fine denier regenerated cellulose fiber has large specific surface area, low bending stiffness, good moisture absorption and air permeability, soft hand feeling, soft and delicate luster, and is more suitable for the processing of high-count yarn and high-end fabrics. The fabrics made by it have the advantages of excellent quality and light texture, and its application range is getting wider and wider.
[0003] When fine and ultrafine denier cellulose fibers are prepared by wet spinning, the total draft is relatively large, but it is generally controlled below 180%. If the total draft is too large, it is easy to cause the fiber dry elongation rate to drop, and it can also easily cause a large number of broken ends. If the total draft is too small, the fiber dry strength is low, and it is easy to produce coarse fibers and parallel yarns, resulting in defective grades. Therefore, when spinning a certain fiber variety, the effective component content of the viscose solution, the selection of the nozzle aperture and the drafting process need to be strictly calculated. Patent CN1418990A discloses the use of high methyl cellulose content (methyl cellulose content 8.99-9.05%, sodium hydroxide 5.53-5.6%), high drafting (total drafting 350-370%), and produces fibers with a fineness of 0.56-0.22 dtex. The large drafting will inevitably cause the breakage of the single filament and the deterioration of the spinnability. The patent does not mention the mechanical strength index. Patent CN1632189A discloses a production technology of high-white, strong, fine-denier viscose staple fibers with a fineness of 0.90-1.40 dtex; CN104790053A discloses a method for making ultra-fine viscose fibers, CN108677273A discloses a method for preparing fine-denier strong yarns, and CN102251301A discloses an ultra-fine-denier high-strength viscose fiber production process. All of them are produced by changing the spinneret aperture, increasing the draft ratio, or using a high wet modulus fiber production process to produce fine-denier fibers. These technologies place higher demands on raw materials, equipment, and process control, which will significantly increase production costs. CN105780184A uses electrospinning technology to prepare fibers using carboxymethyl cellulose (CMC) as raw material. CN105133077A discloses a fine denier cellulose fiber and a preparation method thereof, wherein a functional polymer material and a cellulose solution are co-formed into a spun fiber, and then the functional polymer material in the fiber is removed during post-treatment, thereby reducing the linear density of the fiber to obtain a 0.56-0.89 dtex fine denier cellulose fiber, but the minimum fineness can only be 0.56 dtex, and the functional polymer material needs to be removed separately again later. Summary of the invention
[0004] Based on the above background, the purpose of the present invention is to provide an ultra-fine denier regenerated cellulose fiber and a preparation method thereof, which can reduce the cellulose composition, ensure the drawing plasticity of the system during the spinning process by adding plasticizers and viscosity enhancers, complete the separation of polymer substances and cellulose in the fiber feeding slot CS2 recovery process, reduce the post-processing to remove the polymer substances, and the fineness can reach 0.33-0.55dtex. The fineness of the cellulose fiber is further improved, and an ultra-fine denier regenerated cellulose fiber has been developed.
[0005] The present invention adopts the following technical solutions:
[0006] Disclosed is an ultra-fine regenerated cellulose fiber, the linear density of the fiber is 0.33-0.55 dtex, the dry breaking strength of the fiber is 2.00-2.60 cN / dtex, and the wet breaking strength is 1.00-1.40 cN / dtex.
[0007] A method for preparing ultrafine denier regenerated cellulose fiber comprises the following steps:
[0008] (1) Preparation of blended spinning solution:
[0009] Cellulose xanthate is prepared from cellulose pulp through soaking, pressing, crushing, aging and xanthation.
[0010] Add water-soluble polymer substances and mix them evenly, then add plasticizers and thickeners, dissolve them with sodium hydroxide solution, mix them evenly, and prepare a blended spinning solution;
[0011] (2) Spinning:
[0012] The blended spinning solution is filtered, degassed, and spun to obtain a cellulose fiber bundle;
[0013] (3) Refining treatment:
[0014] The cellulose fiber tow is cut and enters the fiber feeding trough, where it stays for a certain period of time to remove water-soluble polymer substances, and then exits the fiber feeding trough for washing, desulfurization, bleaching, oiling and drying to complete the preparation of ultra-fine denier regenerated cellulose fiber.
[0015] It should be noted that the fiber surface layer coming out of the fiber slot is subjected to processes such as washing, desulfurization, bleaching, oiling, drying and packaging. The specific process control can be the same as the conventional viscose fiber post-processing process according to needs.
[0016] Furthermore, the water-soluble polymer substance is polyvinyl alcohol, and the mass ratio of polyvinyl alcohol to cellulose is 10-45:90-55.
[0017] Furthermore, the plasticizer is glycerol or polyethylene glycol.
[0018] By adding propylene glycol or polyethylene glycol, the molding reaction rate is improved, the intermolecular structure is stabilized, the internal and external molding is uniform, and a buffering effect is played.
[0019] Furthermore, the added amount of glycerol or polyethylene glycol is 1-4% of the mass of cellulose.
[0020] Furthermore, the thickener is carboxymethyl cellulose.
[0021] Furthermore, the added amount of carboxymethyl cellulose is 5-10% of the mass of cellulose.
[0022] Furthermore, in the blended spinning solution, the total content of water-soluble polymer and cellulose is 6.2-8.2%, the content of sodium hydroxide is 4.2-5.0%, and the system viscosity of the blended spinning solution is 60-90s.
[0023] Furthermore, during the spinning process, the temperature of the spinning bath is 48-52°C, and the components include 60-110 g / L sulfuric acid, 15-35 g / L zinc sulfate, and 380-420 g / L sodium sulfate; the nozzle draft of the spinning process is 40-60%, the inter-disk draft is 45-80%, the second bath draft is 9-14%, and the total draft is not higher than 180%.
[0024] Furthermore, the heating steam pressure of the fiber feeding tank is 0.01-0.02Mpa, the water temperature in the fiber feeding tank is ≥98°C, and the residence time of the cut cellulose fiber tow in the fiber feeding tank is 4-9.5min.
[0025] The present invention has the following beneficial effects:
[0026] The fiber linear density is 0.33-0.55dtex, the dry breaking strength is 2.00-2.60cN / dtex, and the wet breaking strength is 1.00-1.40cN / dtex. It is an ultra-fine regenerated cellulose fiber with large specific surface area, low bending stiffness, good moisture absorption and air permeability, soft hand feeling, soft and delicate luster, excellent quality, light texture, and more high-grade fabrics;
[0027] Plasticizers and thickeners are added to the blended spinning solution to ensure high viscosity and spinnability of the system while reducing the cellulose content. The fineness of the selected fiber varieties is further reduced, and the water-soluble polymer substance (polyvinyl alcohol) is removed directly in the fiber feeding tank in the CS2 recovery process, reducing the refining polymer substance removal process and simplifying the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are microscope test images of the regenerated cellulose fibers prepared in Example 1 and conventional cellulose fibers on the market. DETAILED DESCRIPTION
[0029] The present invention will be specifically described below in conjunction with the accompanying drawings:
[0030] As one embodiment thereof, an ultrafine regenerated cellulose fiber has a linear density of 0.33-0.55 dtex, a dry breaking strength of 2.00-2.60 cN / dtex, and a wet breaking strength of 1.00-1.40 cN / dtex.
[0031] As one embodiment thereof, a method for preparing ultrafine denier regenerated cellulose fiber comprises the following steps:
[0032] (1) Preparation of blended spinning solution:
[0033] Cellulose xanthate is prepared from cellulose pulp through soaking, pressing, crushing, aging and xanthation.
[0034] Add water-soluble polymer substances and mix them evenly, then add plasticizers and thickeners, dissolve them with sodium hydroxide solution, mix them evenly, and prepare a blended spinning solution;
[0035] (2) Spinning:
[0036] The blended spinning solution is filtered, degassed, and spun to obtain a cellulose fiber bundle;
[0037] (3) Refining treatment:
[0038] The cellulose fiber tow is cut and enters the fiber feeding trough, where it stays for a certain period of time to remove water-soluble polymer substances, and then exits the fiber feeding trough to be washed, desulfurized, bleached, oiled, dried, and packaged to complete the preparation of ultrafine denier regenerated cellulose fiber.
[0039] As one embodiment, further, the water-soluble polymer substance is polyvinyl alcohol, and the mass ratio of polyvinyl alcohol to cellulose is 10-45:90-55.
[0040] As an embodiment thereof, further, the plasticizer is glycerol or polyethylene glycol.
[0041] As one embodiment, further, the added amount of glycerol or polyethylene glycol is 1-4% of the mass of cellulose.
[0042] As an embodiment thereof, further, the thickener is carboxymethyl cellulose.
[0043] As one embodiment, further, the added amount of carboxymethyl cellulose is 5-10% of the mass of cellulose.
[0044] As one embodiment thereof, further, in the blended spinning solution, the total content of the water-soluble polymer and the cellulose is 6.2-8.2%, the content of sodium hydroxide is 4.2-5.0%, and the system viscosity of the blended spinning solution is 60-90s.
[0045] As one of the embodiments, further, in the spinning process, the temperature of the spinning bath is 48-52°C, and the components include 60-110 g / L sulfuric acid, 15-35 g / L zinc sulfate, and 380-420 g / L sodium sulfate; the nozzle drafting of the spinning process is 40-60%, the inter-disk drafting is 45-80%, the second bath drafting is 9-14%, and the total drafting is not higher than 180%.
[0046] As one embodiment, further, the heating steam pressure of the fiber feeding groove is 0.01-0.02Mpa, the water temperature in the fiber feeding groove is ≥98°C, and the residence time of the cut cellulose fiber tow in the fiber feeding groove is 4-9.5min.
[0047] Embodiment 1:
[0048] 1) Preparation of blended spinning solution
[0049] Polyvinyl alcohol is prepared into a water-soluble solution with a mass concentration of 15%; cellulose pulp is used as a raw material, and cellulose xanthate is obtained through the steps of impregnation, pressing, crushing, aging, and xanthation; polyvinyl alcohol aqueous solution and cellulose xanthate are mixed evenly according to the mass ratio of cellulose: polyvinyl alcohol = 85:15, polyethylene glycol of 2% of the mass of cellulose and carboxymethyl cellulose of 5% of the mass of cellulose are added, and sodium hydroxide solution is used to dissolve and mix evenly. By mass, the total content of polyvinyl alcohol and cellulose in the obtained blended spinning solution is 7.26%, the content of sodium hydroxide is 4.62%, and the viscosity is 76s.
[0050] 2) Spinning
[0051] The blended spinning solution was filtered, degassed, and spun, wherein the spinning bath temperature was 48°C, the components included 65 g / L sulfuric acid, 35 g / L zinc sulfate, and 380 g / L sodium sulfate; the nozzle draft was 60%, the disk draft was 45%, the second bath draft was 9.5%, and the total draft was 157%, thereby obtaining a cellulose fiber tow with a linear density of 0.53 dtex.
[0052] 3) Post-processing
[0053] The cellulose fiber bundle prepared above was cut and entered into the fiber feeding tank. The fiber feeding tank was heated with steam pressure of 0.01Mpa and water temperature of 99℃. The fiber stayed in the fiber feeding tank for 8.5min. The fiber was washed, desulfurized, washed, bleached, oiled, dried and other processes after exiting the fiber feeding tank. The linear density of the obtained fiber was 0.45dtex (see the microscope test picture). Figure 1 As shown, the left side is the regenerated cellulose fiber prepared in this embodiment, and the right side is the conventional cellulose fiber on the market), the dry breaking strength is 2.58 cN / dtex, and the wet breaking strength is 1.26 cN / dtex.
[0054] Embodiment 2:
[0055] 1) Preparation of blended spinning solution
[0056] Polyvinyl alcohol is prepared into a water-soluble solution with a mass concentration of 15%; cellulose pulp is used as a raw material, and cellulose xanthate is obtained through the steps of impregnation, pressing, crushing, aging, and xanthation; polyvinyl alcohol aqueous solution and cellulose xanthate are mixed evenly according to the mass ratio of cellulose: polyvinyl alcohol = 55:45, polyethylene glycol of 3% of the mass of cellulose and carboxymethyl cellulose of 6% of the mass of cellulose are added, and sodium hydroxide solution is used to dissolve and mix evenly. By mass, the total content of polyvinyl alcohol and cellulose in the obtained blended spinning solution is 6.23%, the content of sodium hydroxide is 4.28%, and the viscosity is 65s.
[0057] 2) Spinning
[0058] The blended spinning solution was filtered, degassed, and spun, wherein the spinning bath temperature was 49°C, the components included 86 g / L sulfuric acid, 26 g / L zinc sulfate, and 395 g / L sodium sulfate, the nozzle draft was 42%, the disk draft was 61%, the second bath draft was 12%, and the total draft was 156%, thereby obtaining a cellulose fiber tow with a linear density of 0.61 dtex.
[0059] 3) Post-processing
[0060] The cellulose fiber tow prepared above was cut and entered into the fiber feeding tank, the fiber feeding tank was heated with steam pressure of 0.02Mpa, the water temperature in the fiber feeding tank was 99°C, and the fiber stayed in the fiber feeding tank for 4 minutes. The fiber was washed, desulfurized, washed, bleached, oiled, dried, etc. after exiting the fiber feeding tank. The linear density of the prepared fiber was 0.33dtex, the dry breaking strength was 2.46cN / dtex, and the wet breaking strength was 1.33cN / dtex.
[0061] Embodiment 3:
[0062] 1) Preparation of blended spinning solution
[0063] Polyvinyl alcohol is prepared into a water-soluble solution with a mass concentration of 15%; cellulose pulp is used as a raw material, and cellulose xanthate is obtained through the steps of impregnation, pressing, crushing, aging, and xanthation; polyvinyl alcohol aqueous solution and cellulose xanthate are mixed evenly according to the mass ratio of cellulose: polyvinyl alcohol = 90:10, polyethylene glycol of 1% of the mass of cellulose and carboxymethyl cellulose of 8% of the mass of cellulose are added, and sodium hydroxide solution is used to dissolve and mix evenly. By mass, the total content of polyvinyl alcohol and cellulose in the obtained blended spinning solution is 8.2%, the content of sodium hydroxide is 5.0%, and the viscosity is 90s.
[0064] 2) Spinning
[0065] The blended spinning solution was filtered, degassed, and spun, wherein the spinning bath temperature was 49°C, the components included 86 g / L sulfuric acid, 26 g / L zinc sulfate, and 415 g / L sodium sulfate, the nozzle draft was 40%, the disk draft was 72%, the second bath draft was 13.5%, and the total draft was 174%, thereby obtaining a cellulose fiber tow with a linear density of 0.62 dtex.
[0066] 3) Post-processing
[0067] The cellulose fiber tow prepared above was cut and entered into the fiber feeding tank, the fiber feeding tank was heated with steam pressure of 0.02Mpa, the water temperature in the fiber feeding tank was 100℃, and the fiber stayed in the fiber feeding tank for 6.5min. The fiber was washed, desulfurized, washed, bleached, oiled, dried, etc. after exiting the fiber feeding tank. The linear density of the prepared fiber was 0.55dtex, the dry breaking strength was 2.60cN / dtex, and the wet breaking strength was 1.39cN / dtex.
[0068] Embodiment 4:
[0069] 1) Preparation of blended spinning solution
[0070] Polyvinyl alcohol is prepared into a water-soluble solution with a mass concentration of 15%; cellulose pulp is used as a raw material, and cellulose xanthate is obtained through the steps of impregnation, pressing, crushing, aging, and xanthation; polyvinyl alcohol aqueous solution and cellulose xanthate are mixed evenly according to the mass ratio of cellulose: polyvinyl alcohol = 70:30, polyethylene glycol of 4% of the mass of cellulose and carboxymethyl cellulose of 6% of the mass of cellulose are added, and sodium hydroxide solution is used to dissolve and mix evenly. By mass, the total content of polyvinyl alcohol and cellulose in the obtained blended spinning solution is 7.88%, the content of sodium hydroxide is 4.86%, and the viscosity is 76s.
[0071] 2) Spinning
[0072] The blended spinning solution was filtered, degassed, and spun, wherein the spinning bath temperature was 52°C, the components included 110 g / L sulfuric acid, 15 g / L zinc sulfate, and 420 g / L sodium sulfate; the nozzle draft was 45%, the disk draft was 63%, the second bath draft was 14%, and the total draft was 167%, thereby obtaining a cellulose fiber tow with a linear density of 0.59 dtex.
[0073] 3) Post-processing
[0074] The cellulose fiber tow prepared above was cut and entered into the fiber feeding tank, the fiber feeding tank was heated with steam pressure of 0.02Mpa, the water temperature in the fiber feeding tank was 100℃, and the fiber stayed in the fiber feeding tank for 7.5min. The fiber was washed, desulfurized, washed, bleached, oiled, dried, etc. after exiting the fiber feeding tank. The linear density of the prepared fiber was 0.42dtex, the dry breaking strength was 2.23cN / dtex, and the wet breaking strength was 1.19cN / dtex.
[0075] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing ultrafine denier regenerated cellulose fiber, characterized in that: The following steps are involved: (1) Preparation of blended spinning solution: Cellulose xanthate is prepared from cellulose pulp through soaking, pressing, crushing, aging and xanthation. Add water-soluble polymer substances and mix them evenly, then add plasticizers and thickeners, dissolve them with sodium hydroxide solution, mix them evenly, and prepare a blended spinning solution; The plasticizer is polyethylene glycol; The amount of polyethylene glycol added is 1-4% of the cellulose mass; The thickener is carboxymethyl cellulose; The amount of carboxymethyl cellulose added is 5-10% of the cellulose mass; (2) Spinning: The blended spinning solution is filtered, degassed, and spun to obtain a cellulose fiber bundle; During spinning, the temperature of the spinning bath is 48-52°C, and the components include 60-110g / L sulfuric acid, 15-35g / L zinc sulfate, and 380-420g / L sodium sulfate; the nozzle draft of the spinning is 40-60%, the inter-disk draft is 45-80%, the second bath draft is 9-14%, and the total draft is not higher than 180%; (3) Refining treatment: The cellulose fiber tow is cut and enters the fiber feeding tank, where it stays for a certain period of time to remove water-soluble polymer substances, and then exits the fiber feeding tank, and is washed, desulfurized, bleached, oiled, and dried to complete the preparation of ultra-fine denier regenerated cellulose fiber; The prepared ultrafine regenerated cellulose fiber has a linear density of 0.33-0.55 dtex, a dry breaking strength of 2.00-2.60 cN / dtex, and a wet breaking strength of 1.00-1.40 cN / dtex.
2. The method for preparing ultrafine denier regenerated cellulose fiber according to claim 1, characterized in that: The water-soluble polymer substance is polyvinyl alcohol, and the mass ratio of polyvinyl alcohol to cellulose is 10-45:90-55.
3. The method for preparing ultrafine denier regenerated cellulose fiber according to claim 1, characterized in that: In the blended spinning solution, the total content of water-soluble high molecular weight substances and cellulose is 6.2-8.2% by mass, the content of sodium hydroxide is 4.2-5.0%, and the system viscosity of the blended spinning solution is 60-90s.
4. The method for preparing ultrafine denier regenerated cellulose fiber according to claim 1, characterized in that: The heating steam pressure of the fiber feeding tank is 0.01-0.02Mpa, the water temperature in the fiber feeding tank is ≥98°C, and the residence time of the cut cellulose fiber tow in the fiber feeding tank is 4-9.5min.
Citation Information
Patent Citations
Production process of ultrafine-denier high-strength viscose fibers
CN102251301A
Method for manufacturing superfine denier viscose fibers
CN104790053A
Method for preparing fiber from carboxymethyl cellulose (CMC) by electrostatic spinning
CN105780184A
Method for preparing fine denier strong viscose fibers
CN108677273A
Ultralow denier fibre for viscose chemical fibre
CN1418990A